PERIPHYLLUS CALIFORNIENSIS (SHINJI, 1917) AND TINOCALLIS SALTANS (NEVSKY, 1929) (HEMIPTERA: APHIDIDAE), TWO ALIEN APHID SPECIES NEW TO THE FAUNA OF SERBIA (Acta Entomologica Serbica, 2022)
This paper presents two alien species of aphids new to the fauna of Serbia with details on their morphology and biology, with original photographs. Periphyllus californiensis (Shinji, 1917) is an invasive species that belongs to the subfamily Chaitophorinae and was found for the first time in 2021 on Acer palmatum Thunb. Tinocallis saltans (Nevsky, 1929) belongs to the subfamily Calaphidinae and was found on Ulmus pumila L. in 2020 and 2021. Both species were registered in Belgrade. There is now a total of 393 registered species of aphids in Serbia.